The notion of inscripturation - WJ Ouweneel (Acta Theologica)
Even if the following reasoning is a priori determined by my faith-conviction concerning its outcome, i.e. even if I cannot escape from my "hermeneutical circle", I may still reason in the following way (cf. Ott, 1972:45; Berkhof, 1985:81f; Potgieter, 1990:18).